Recommended practices for laser beam welding, cutting, and allied processes (American Welding Society, 2010)
This document presents recommended practices for laser beam welding, cutting, drilling, and transformation hardening. It is intended to cover common applications of the process. Processes definitions, safe practices, general process requirements and inspection criteria are provided.